2005
DOI: 10.1073/pnas.0501999102
|View full text |Cite
|
Sign up to set email alerts
|

The human Kv1.1 channel is palmitoylated, modulating voltage sensing: Identification of a palmitoylation consensus sequence

Abstract: The functional sequelae of palmitoylation were examined by analysis of whole cell currents from WT and mutant channels, which identified a 20-mV leftward shift in the current-voltage relationship when palmitoylation at C243 (but not with other cysteine deletions) is prevented by site-directed mutagenesis, implicating a role for palmitoylated C243 in modulating voltage sensing through protein-membrane interactions. Database searches identified an amino acid palmitoylation consensus motif (ACP͞RSKT) that is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 47 publications
0
66
0
Order By: Relevance
“…This raises the possibility that regulation of delayed rectifier, voltage-gated K channels by iPLA 2 ␤, or products of its action might be a phenomenon that is not confined to ␤-cells. Kv1.1 channel activity (66) and subcellular location (67) are also affected by free fatty acids, and it is possible that colocalization or direct interaction of iPLA 2 ␤ and voltage-gated K channels, such as Kv1.1 and Kv2.1, occur.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that regulation of delayed rectifier, voltage-gated K channels by iPLA 2 ␤, or products of its action might be a phenomenon that is not confined to ␤-cells. Kv1.1 channel activity (66) and subcellular location (67) are also affected by free fatty acids, and it is possible that colocalization or direct interaction of iPLA 2 ␤ and voltage-gated K channels, such as Kv1.1 and Kv2.1, occur.…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphorylation is a fundamental mechanism to control ion channel function, and increasing evidence suggests that multiple ion channels are also regulated by palmitoylation (16)(17)(18)(19)(20)(21). We would predict that phosphorylationpalmitoylation cross-talk is likely to occur when sites of palmitoylation are flanked by sites of serine/threonine phosphorylation.…”
Section: Pka Phosphorylation Dissociates the Strex C Terminus From Thementioning
confidence: 99%
“…Catalytic subunit of PKAc was from Promega. The 8-CPT-cGMP, 8-CPT-cAMP, KT5823, chelerythrine chloride, KN-62, and PKI [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] were from Calbiochem.…”
Section: Palmitoylation Prediction and Palmitoylation Assays Css-palmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ion channels are integral parts of the cell signaling machinery, only a few studies have identified ion channel palmitoylation (13,(19)(20)(21)(22). Furthermore, no information on direct myristoylation of any ion channel has been reported yet.…”
Section: Discussionmentioning
confidence: 99%